2004
DOI: 10.1002/fuce.200400060
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Methanol Permeability and Structure of Different Radiation‐Grafted Membranes

Abstract: Styrene grafted and sulfonated poly(vinylidene fluoride) and poly(vinylidene fluoride‐co‐hexafluoropropylene) films are candidates as electrolytes in direct methanol fuel cells. Their behaviour in water, 1 and 3 mol dm–3 aqueous methanol, and pure methanol were studied. According to SAXS results, water and methanol‐water solutions have similar effects on the membranes, i.e., the lamellar period increases and the ionic domains enlarge. Furthermore, differences in the ionic domain structures in pure methanol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Therefore, decrease in the liquid water uptake impedes methanol transport through the coated Nafion. Methanol diffusion coefficients and permeability have also been earlier shown to decrease with the decreasing water uptake of an ion exchange membrane [28]. Similar trend has been observed for oxygen transport through Nafion as it is faster through the hydrophilic water channel phase than through the another phase of the membrane comprising of the hydrophobic backbones of the Nafion molecule chains [37].…”
Section: Crossover Measurements In a Fuel Cellsupporting
confidence: 63%
See 1 more Smart Citation
“…Therefore, decrease in the liquid water uptake impedes methanol transport through the coated Nafion. Methanol diffusion coefficients and permeability have also been earlier shown to decrease with the decreasing water uptake of an ion exchange membrane [28]. Similar trend has been observed for oxygen transport through Nafion as it is faster through the hydrophilic water channel phase than through the another phase of the membrane comprising of the hydrophobic backbones of the Nafion molecule chains [37].…”
Section: Crossover Measurements In a Fuel Cellsupporting
confidence: 63%
“…The drag correction factor kdl is taken from the data in ref. [28] as a function of temperature in 1 M MeOH: 0.8592 at 30°C…”
Section: Performance and Permeability Measurements In A Methanol Or Hmentioning
confidence: 99%
“…On the other hand, some part of this gain is lost as the MeOH crossover also increases as a function of temperature [27,29].…”
Section: The Effect Of Cell Temperaturementioning
confidence: 96%
“…In the case of the DMFC, the MeOH crossover (MeOH permeability through the membrane) is a very dominating loss mechanism [17] and it has been investigated widely [18][19][20][21][22][23][24][25][26][27][28][29]. However, most of these studies have been performed without current distribution measurements.…”
Section: Introductionmentioning
confidence: 98%
“…Other research works, have demonstrated that sulfonated partially fluorinated PEMs based on styrene-grafted membranes have similar or higher performance in direct methanol fuel cells (DMFC) [4,8].…”
Section: Introductionmentioning
confidence: 99%